Insights into trehalose mediated physiological and biochemical mechanisms in Zea mays L. under chromium stress - Sadia Zafar; Inam Mehdi Khan; Muhammad Arslan Ashraf; Muhammad Zafar; Mushtaq Ahmad; Rizwan Rasheed; Ansar Mehmood; Khawaja Shafique Ahmad (BMC Plant Biology, 2024)
Abstract Background Chromium (Cr) toxicity significantly threatens agricultural ecosystems worldwide, adversely affecting plant growth and development and reducing crop productivity. Trehalose, a non-reducing sugar has been identified as a mitigator of toxic effects induced by abiotic stressors such as drought, salinity, and heavy metals. The primary objective of this study was to investigate the influence of exogenously applied trehalose on maize plants exposed to Cr stress. Results Two maize varieties, FH-1046 and FH-1453, were subjected to two different Cr concentrations (0.3 mM, and 0.5 mM). The results revealed significant variations in growth and biochemical parameters for both maize varieties under Cr-induced stress conditions as compared to the control group. Foliar application of trehalose at a concentration of 30 mM was administered to both maize varieties, leading to a noteworthy reduction in the detrimental effects of Cr stress. Notably, the Cr (0.5 mM) stress more adversely affected the shoot length more than 0.3mM of Cr stress. Cr stress (0.5 mM) significantly reduced the shoot length by 12.4% in FH-1046 and 24.5% in FH-1453 while Trehalose increased shoot length by 30.19% and 4.75% in FH-1046 and FH-1453 respectively. Cr stress significantly constrained growth and biochemical processes, whereas trehalose notably improved plant growth by reducing Cr uptake and minimizing oxidative stress caused by Cr. This reduction in oxidative stress was evidenced by decreased production of proline, SOD, POD, MDA, H2O2, catalase, and APX. Trehalose also enhanced photosynthetic activities under Cr stress, as indicated by increased values of chlorophyll a, b, and carotenoids. Furthermore, the ameliorative potential of trehalose was demonstrated by increased contents of proteins and carbohydrates and a decrease in Cr uptake. Conclusions The study demonstrates that trehalose application substantially improved growth and enhanced photosynthetic activities in both maize varieties. Trehalose (30 mM) significantly increased the plant biomass, reduced ROS production and enhanced resilience to Cr stress even at 0.5 mM.